1992
DOI: 10.1073/pnas.89.4.1253
|View full text |Cite
|
Sign up to set email alerts
|

Restricted heterogeneity in T-cell antigen receptor V beta gene usage in the lymph nodes and arthritic joints of mice.

Abstract: We have used PCR to study the expression of T-cell antigen receptor 13 RNA containing particular variable region (V) elements from transcripts directly in the cells isolated from joints and lymph nodes of B1O.Q mice (H-2r) immunized with chicken type II collagen. Our data show that the T cells present in arthritic joints expressed only a few '$ transcripts -'2, -6, -7, -8.2, -9, -10, and -15. 6 and -8.2 were expressed predominantly (six out ofseven animals) while others were expressed at a relatively low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 12 publications
3
43
0
Order By: Relevance
“…The present study showed that VpS-negative (RIIIS x C57BR)F, mice also develop arthritis (Table I), and other studies indicate that RIIIS mice which lack both Vp6 and Vp8 develop a mild, transient CIA (30). Recent work by Haqqi et al supports these findings and suggests that Vp6, Vp8.2, Vp7, and Vp9 are involved in CIA since these T cells are the ones most commonly found in the joints and draining lymph nodes of Bl0.Q mice with CIA (33).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The present study showed that VpS-negative (RIIIS x C57BR)F, mice also develop arthritis (Table I), and other studies indicate that RIIIS mice which lack both Vp6 and Vp8 develop a mild, transient CIA (30). Recent work by Haqqi et al supports these findings and suggests that Vp6, Vp8.2, Vp7, and Vp9 are involved in CIA since these T cells are the ones most commonly found in the joints and draining lymph nodes of Bl0.Q mice with CIA (33).…”
Section: Discussionsupporting
confidence: 59%
“…In the CIA model, mice or rats immunized with heterologous or homologous collagen develop an acute-to-chronic polyarthritis thought to be mediated by T cells that are cross-reactive with self collagen as well as by an antibody response to specific collagen epitopes (23)(24)(25)(26)(27). T cells bearing the Vp8 TCRs have been shown to play a major role in CIA (18,28), and there is some evidence that other TCRs, such as Vp5, Vp6, and Vp7, may also be involved, especially in mouse strains that lack VpS (28)(29)(30)(31)(32)(33).…”
mentioning
confidence: 99%
“…All lymphomas had evidence of a T-cell lineage by one of these markers. Likewise, clonality was determined by TCRb rearrangement and expression as described (Haqqi, et al 1992). All lymphomas had TCRb clonal rearrangments by Southern analysis (data not shown).…”
Section: K-ras Mutations Following Mnumentioning
confidence: 98%
“…The hypofunction of the salivary and lachrymal glands in autoimmune disease is due to lymphocytic infiltration, in which it is generally assumed that autoreactive T cells recognize unknown self-antigen and play a central role in the pathogenesis of SS [22]. Clonally expanded T cell populations having restricted usage of TCR gene segments may be essential to the pathogenesis of autoimmune diseases [23,24]. The restriction of TCR repertoire may play an important role in T cell recognition of unknown self antigen through a possible restrictive usage of TCR Vb genes in various autoimmune diseases, both in humans and rodents.…”
Section: Discussionmentioning
confidence: 99%